Clinical Anatomy. Errors in performing neck operations article - Donayev Makhmud, Gadayev Asliddin (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2023)
Performing neck operations requires a high level of precision and expertise. Any errors during these surgeries can have severe consequences for the patient. Here are some common errors that can occur during neck operations